ChemInform Abstract: [Bmim][InCl4]‐Catalyzed Addition of Hydrazones to β‐Diketones: An Efficient Regioselective Synthesis of Pyrazoles and Pyrazole‐Fused Cyclohexanones. Issue 39 (5th September 2013) - Safaei, Shirin; Mohammadpoor‐Baltork, Iraj; Khosropour, Ahmad Reza; Moghadam, Majid; Tangestaninejad, Shahram; Mirkhani, Valiollah; Khavasi, Hamid Reza
Abstract Among different Lewis acids tested as promoters, good yield and the best regioselectivity is achieved with [bmim]InCl4.